Effectiveness of intrapartum antibiotic prophylaxis for early-onset group B Streptococcal infection: An integrative review. Issue 4 (August 2018) - Braye, Kathryn; Ferguson, John; Davis, Deborah; Catling, Christine; Monk, Amy; Foureur, Maralyn
Abstract: Background: In some countries, up to 30% of women are exposed to intrapartum antibiotic prophylaxis for prevention of early-onset group B Streptococcal infection. Intrapartum antibiotic prophylaxis aims to reduce the risk of neonatal morbidity and mortality from this infection. The intervention may adversely affect non-pathogenic bacteria which are passed to the newborn during birth and are considered important in optimising health. Since many women are offered intrapartum antibiotic prophylaxis, effectiveness and implications of this intervention need to be established. This review considers clinical trials and observational studies analysing the effectiveness of intrapartum antibiotic prophylaxis. Methods: An integrative literature review was conducted. One systematic review, three clinical trials and five observational studies were identified for appraisal. Findings: Randomised controlled trials found intrapartum antibiotic prophylaxis effective but all retrieved randomised clinical trials had significant methodological flaws. High quality observational studies reported high rates of effectiveness but revealed less than optimal adherence to screening and administration of the prophylaxis. Scant consideration was given to short term risks, and long-term consequences were not addressed. Discussion: Studies found intrapartum antibiotic prophylaxis to be effective. However, evidence was not robust and screening and prophylaxis have limitations. Emerging evidence links intrapartum antibiotic prophylaxis to adverse short and longer-term neonatal outcomes. Conclusion: Our review found high quality evidence of the effectiveness of intrapartum antibiotic prophylaxis was limited. Lack of consideration of potential risks of the intervention was evident. Women should be enabled to make informed decisions about GBS management. More research needs to be done in this area.